Close Association of HLA-B52 and HLA-B44 Antigens in Israeli Arab Adolescents With Recurrent Aphthous Stomatitis - Jaber, Lutfi; Weinberger, Abraham; Klein, Tirza; Yaniv, Isaac; Mukamel, Masza (Archives of otolaryngology--head & neck surgery, 2001)
OBJECTIVES To investigate the incidence and clinical features of recurrent aphthous stomatitis (RAS) among Israeli Arab adolescents and to determine the HLA typing profile in affected subjects. STUDY DESIGN Cross-sectional study. SETTING Junior high school in the largest Arab town in Israel. PARTICIPANTS Four hundred seventy-seven Israeli Arab junior high school students filled out a questionnaire. Students who reported more than 4 episodes of RAS during the previous year were interviewed by telephone. Those whose responses were confirmed were invited to the clinic. Of these, 22 were chosen at random for HLA typing. Findings were compared with those in 117 healthy Israeli Arabs who were candidate donors of bone marrow to patients at the Institute of Hematology–Oncology, Schneider Children's Medical Center of Israel, Petah Tiqva. RESULTS Recurrent aphthous stomatitis was confirmed in 80 subjects (16.7%). Of the 22 patients who underwent HLA typing, 7 (31.4%) had HLA-B52 antigens and 8 (36.4%) had HLA-B44 antigens; corresponding figures for the control group were 10 subjects (8.5%) (P = .007) and 9 subjects (7.7%) (P = .001), respectively. CONCLUSIONS There is a close association of HLA-B52 and HLA-B44 in Israeli Arab youths with RAS. Long-term follow-up is needed to determine the relationship between RAS and Behçet disease.Arch Otolaryngol Head Neck Surg. 2001;127:184-187-->